2000
DOI: 10.1046/j.1365-2656.2000.00422.x
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent breeding in the short‐tailed shearwaterPuffinus tenuirostris

Abstract: Summary1. At one colony of short-tailed shearwaters in Bass Strait, Australia, all birds breeding have been recorded individually each year for over 50 years. Among individuals known to be alive and to have bred before, 14% of each sex were not present at their breeding colony, on average, in any one year. 2. A further 15% of males and 13% of females (a signi®cant dierence), known to have bred before, were present but not associated with an egg in any one year. 3. Intermittent breeding was associated with pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…Increased frequency of skipping in the oldest age classes has also been reported in great skuas Catharacta skua (Catry et al, 1998), European shags (Harris et al, 1998) and short-tailed shearwaters Puffinus tenuirostris (Bradley et al, 2000). These patterns collectively point toward reproductive senescence effects in long-lived seabirds and clearly warrant further investigation.…”
Section: Discussionmentioning
confidence: 62%
“…Increased frequency of skipping in the oldest age classes has also been reported in great skuas Catharacta skua (Catry et al, 1998), European shags (Harris et al, 1998) and short-tailed shearwaters Puffinus tenuirostris (Bradley et al, 2000). These patterns collectively point toward reproductive senescence effects in long-lived seabirds and clearly warrant further investigation.…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies found that intermittent breeding was unrelated to environmental factors but seemed to be rather a consequence of heterogeneity in individual quality (e.g. [5]). On the contrary, our results revealed that intermittent breeding in redfooted boobies was highly influenced by environmental conditions.…”
Section: Discussionmentioning
confidence: 96%
“…Such studies have quantified intermittent breeding but did not identify correlated environmental mechanisms (e.g. [5]). Individual heterogeneity [6] and density dependence on breeding grounds [7] have been shown to influence recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…Coulson and Thomas 1985;Croxall et al 1992;Sydeman and Eddy 1995;Wendeln and Becker 1999). Likewise, some studies reported higher survival rates for birds with better breeding performance (Ollason and Dunnet 1988;Bradley et al 1989;Mills 1989;Cam and Monnat 2000a). Thus, associations between breeding performance and survival or recruitment age may result in variation in age-specific patterns observed at the population level, regardless of age-related changes within individuals (e.g.…”
Section: Introductionmentioning
confidence: 99%